The Integration of Internet of Things (IoT) in Engineering Management - Mohammadkhani, Ali (Management Strategies and Engineering Sciences, 2021)
The integration of the Internet of Things (IoT) in engineering management has emerged as a transformative force, enabling real-time monitoring, predictive maintenance, and enhanced decision-making. This narrative review synthesizes the current state of IoT integration within engineering management, examining its applications, impacts, and challenges. Through a detailed analysis of existing literature, this study highlights the significant benefits of IoT in improving efficiency and resource optimization, while also addressing the technical and organizational barriers to successful implementation. The findings indicate that while IoT offers substantial advantages, its integration is contingent upon overcoming challenges related to data security, interoperability, and the need for upskilling. The review concludes with implications for practice and research, emphasizing the need for further studies on the long-term impacts of IoT and its intersection with other emerging technologies in engineering management.